Nowe kraje członkowskie Unii Europejskiej w procesach regionalnej integracji gospodarczej i globalizacji - Misala, Józef (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article deals with basic problems of European Union member countries' participation in the interconnected processes of regional economic integration and globalization. It starts with an overview of redirection of these countries' economic relations towards the European Union with special regard to foreign trade and capital flows. Then follows an assessment of new European Union member countries' participation in the international division of labour taking into account several aspects of internationalization on the markets of goods, services, and foreign direct investments. Some conclusions are formulated as a result of respective statistical analyses. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 224-240